Outcomes of professional misconduct by nurses: a qualitative study - Shokoh Varaei; Nahid Dehghan Nayeri; Leila Sayadi; Mehraban Shahmari; Akram Ghobadi (BMC, 2024)
Abstract Background Professional misconduct by nurses is a critical challenge in providing safe quality care, which can lead to devastating and extensive outcomes. Explaining the experiences of clinical nurses and nursing managers in this regard using an in-depth qualitative method can be beneficial. This study was conducted with the aim of explaining the experiences of nurses regarding the outcomes of professional misconduct. Methods The present study used a qualitative descriptive with a conventional content analysis approach. A total of 22 clinical nurses and nursing managers were selected through purposive sampling until data saturation was reached. Data were collected using semi-structured in-depth interviews and analyzed using Graneheim and Lundman's approach. Results Analyzed data were categorized into four main themes and 11 subthemes: (1) Physical outcomes: critical threat and weakening patients' safety; (2) Psychological outcomes: psycho-emotional responses of patients and their families, moral distress, and cautionary tale of nurses; (3) Financial outcomes: imposing costs on the patient and financial loss of the nurse; (4) Organizational outcomes: the normalization of misconduct, chaos in the organization, waste of the organization's resources, and reputational damage to the organization. Conclusion Professional misconduct by nurses can have adverse outcomes for patients in physical, mental, and financial dimensions, their families, nurses, and healthcare organizations. Therefore, it is indispensable to adopt management strategies to reduce the rate of professional misconduct.